Self-control as a mediator of the effects of smartphone addiction and peer attachment on adolescent phubbing behavior - Syifa', Farichah Nurus; Sri Lestari (Indonesian Psychological Research, 2026)
Phubbing, defined as disregarding ongoing social interactions by directing attention to a cellphone, has been associated with various negative consequences, including adverse physical and psychological outcomes and a decline in the quality of adolescents’ social relationships. Although phubbing has attracted considerable scholarly attention, research that explores the personal and environmental factors contributing to this behavior remains limited. This study aims to investigate the role of self-control in mediating the effect of smartphone addiction and peer attachment on phubbing behavior among adolescents. Using multistage cluster sampling technique, data were collected from 260 adolescents using the Phubbing Scale, the Smartphone Addiction Scale Short Version (SAS SV), the Inventory of Parent and Peer Attachment (IPPA), and the Brief Self Control Scale (BSCS). Path analysis was applied to examine the relationships among variables. The results showed that self-control significantly mediated the relationship between smartphone addiction, peer attachment and adolescent phubbing behavior. These findings highlight the central role of self-control in explaining how personal characteristics and environmental influences contribute to phubbing. The study underscores the importance of fostering self-control as a crucial factor in reducing phubbing behavior among adolescents, thereby supporting the development of warm and meaningful social relationships.